Ventajas y desventajas del bachillerato internacional en el sistema educativo nacional - Ulloa Ballesteros, Elisa Soledad (2020)
Resumen:The present essay entitled "Advantages and disadvantages of the International Baccalaureate in the national educational system" is a study on the implementation of the Diploma Programme (DP) in public schools in Ecuador, compared to private institutions. The essay has been written with the aim of visualizing the advantages and disadvantages of offering international educational programs, articulated to the national education system. The study analyzes advantages and disadvantages in aspects such as the design and structure of public schools, the improvement in pedagogical practice, the culture of the schools, the educational offer, the evaluation and the curricular design, reviewing the application of the regulations for the implementation of the International Baccalaureate (IB), issued by the International Baccalaureate Organization and the Ministry of Education of Ecuador.